Method for analyzing lithium from lithium-rich adsorbent of aluminum oxide plant
Through multi-stage countercurrent washing and layered pretreatment of the alumina plant lithium-rich adsorbent, combined with primary thermal analysis and desulfurization and decarbonization, the problems of low lithium analysis efficiency and high energy consumption in the alumina plant are solved, and high efficiency is achieved. The lithium analysis process with low energy consumption can obtain a high concentration and low impurities.
Patent Information
- Application Number
- CN202411370124.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The method of analyzing lithium from lithium-rich adsorbents in the prior art has problems such as high energy consumption, low analytical efficiency and complex process. In particular, resolving and multiple analysis have high energy consumption requirements and high-temperature calcination consumption. A lot of energy.
The lithium-rich adsorbent after continuous multi-stage countercurrent washing is used for layered pretreatment, and through a thermal analysis process, combined with desulfurization and decarbonization, an adsorbent with a layered structure is obtained, and the hydrothermal transformation process is used to achieve efficient analysis of lithium. Reduce energy investment.
The lithium-rich solution is achieved (resolution rate >90%), which reduces energy consumption, simplifies the process, and improves mechanical stability and analytical efficiency. The lithium concentration of the lithium-rich solution obtained is not less than 1g/L, and the impurity content is not less than 1g/L. Low.
Smart Images

Figure CN119242952A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium analysis and separation, and relates to a method for analyzing lithium from a lithium-rich adsorbent in an alumina plant. Background Art
[0002] my country's lithium resources mainly come from salt lake lithium and ore lithium. Among them, the lithium extraction from brine of Qinghai Salt Lake and Tibet Salt Lake mainly adopts the "adsorption method + membrane method", that is, the adsorption method is first used to preferentially adsorb lithium, and then it is analyzed. The lithium ions in the analysis solution are purified by nanofiltration membrane, and then initially concentrated by reverse osmosis, and finally evaporated and precipitated to obtain lithium carbonate.
[0003] The lithium ore in my country is mainly composed of lepidolite. After beneficiation, the lithium oxide content is generally around 1.5%, and a large amount of tailings will be produced during the beneficiation process. The lithium extraction process of lepidolite mainly adopts the method of "calcination + water leaching evaporation", that is, the sulfate is mixed with mica powder and then calcined in a high-temperature kiln, then leached with water, chemically removed, and lithium carbonate is obtained through multiple evaporation precipitation. This process has high energy consumption, and due to the influence of mixed salts, the precipitation efficiency of lithium carbonate is low. In addition, it is also restricted by heavy metals such as beryllium and thallium in the leaching solution, and a large amount of slag is produced, which has a great impact on the ecological environment.
[0004] The development of lithium-powered vehicles has increased my country's demand for lithium resources. Therefore, in addition to deepening the development of salt lake lithium and ore lithium, new sources of lithium have attracted attention.
[0005] We have abundant bauxite resources. The Bayer process based on the "alkali dissolution-seed separation" technology is the main process for the utilization of aluminum resources. That is, the aluminum oxide in the bauxite is dissolved by alkali solution under high temperature and high pressure, and then separated to obtain aluminum hydroxide, and then the aluminum hydroxide is calcined to obtain alumina, and then metallic aluminum is obtained through electrolysis. Geological literature reports that my country's bauxite contains a certain amount of lithium resources. This part of lithium enters the aluminum hydroxide during the Bayer process, and will eventually be enriched in the electrolytic cell, deteriorating the operation of the electrolytic cell. Therefore, extracting this part of lithium can not only supplement my country's lithium resources, but also improve the efficiency of electrolytic aluminum and the quality of aluminum hydroxide.
[0006] Invention patent CN109650413A discloses a method and system for enriching lithium from sodium aluminate solution in an alumina plant, using aluminum hydroxide to adsorb lithium ions, and enriching lithium adsorbents through secondary re-dissolution. Invention patent 109761249A discloses a method and system for analyzing lithium in lithium-rich adsorbents in an alumina plant, using multiple countercurrent or cocurrent hydrothermal analyses, requiring at least 2 or more analysis processes, and increasing the lithium analysis rate to more than 90%. However, the re-dissolution and multiple analyses in this method have high energy consumption requirements, and the analysis efficiency is still limited. Invention patent CN116623010A discloses a method for analyzing lithium from lithium-rich adsorbents in an alumina plant, using a high-temperature calcination crystallization process for analysis, but high-temperature calcination is accompanied by a large amount of energy consumption.
[0007] Therefore, it is necessary to develop a method for analyzing lithium from lithium-rich adsorbents in alumina plants, with low energy consumption, high analysis efficiency and simple process. Summary of the invention
[0008] The object of the present invention is to provide a method for analyzing lithium from a lithium-rich adsorbent in an alumina plant, wherein the lithium concentration in the obtained lithium-rich analysis solution is not less than 1 g / L, and the impurity content is low, the analysis efficiency is high, the process is simple, there is no high-temperature calcination process, and the energy consumption is low.
[0009] The purpose of the present invention can be achieved through the following technical solutions:
[0010] A method for decomposing lithium from a lithium-rich adsorbent in an alumina refinery, comprising the following steps:
[0011] S1. Washing of lithium-rich adsorbent:
[0012] The lithium-rich adsorbent is washed with deionized water by a disc or crawler vacuum filter in a continuous multi-stage countercurrent washing manner, and the washing liquid of the previous stage washes the adsorbent of the next stage to obtain the washed lithium-rich adsorbent and the final washing liquid;
[0013] S2, layered preprocessing:
[0014] At 20 to 80° C., the washed lithium-rich adsorbent is immersed in a pretreatment solution for 0.2 to 5 hours, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with an acidic solution to obtain an activated slurry, wherein the solid content of the activated slurry is 6 to 50%;
[0015] S3. Thermal analysis of activated slurry:
[0016] The activated slurry obtained in S2 is heated to 95-290° C., kept at this temperature for 1-5 hours, and then cooled to 50-70° C. to obtain an analyzed adsorbent and a lithium-rich solution through solid-liquid separation;
[0017] S4, washing:
[0018] The analyzed adsorbent obtained in step S3 is subjected to multi-stage washing to obtain an empty adsorbent and a washing solution, and the washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0019] As a preferred technical solution of the present invention, in step S1, the lithium-rich adsorbent is a lithium-aluminum composite adsorbent, which is composed of (Li x Al y (OH) z CO 3 ), wherein x=0.5-2, y=0.1-2, z=0.3-4.5, and contains 0.1-5% sulfur or sulfide.
[0020] As a preferred technical solution of the present invention, in step S1, the number of stages of the continuous multi-stage countercurrent washing is 3 to 5.
[0021] As a preferred technical solution of the present invention, in step S1, the final washing liquid is a sodium aluminate solution with a mass fraction of 5 to 20%.
[0022] As a preferred technical solution of the present invention, in step S2, the pretreatment liquid is an oxidizing solution with a mass fraction of 5 to 20%, which is one or more of hydrogen peroxide, sodium hypochlorite and nitric acid.
[0023] As a preferred technical solution of the present invention, in step S2, the acidic solution is one or more of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.
[0024] As a preferred technical solution of the present invention, in step S2, the pH value of the activated slurry is 1.4-4.9.
[0025] As a preferred technical solution of the present invention, the equipment used for heating in step S3 is a kettle hydrothermal reactor or a pipeline hydrothermal reactor.
[0026] As a preferred technical solution of the present invention, in step S4, the multi-stage washing method is to use a tank reactor for stirring washing or a vacuum crawler type for elution washing.
[0027] As a preferred technical solution of the present invention, in step S4, the multi-stage washing is first soaked in pure water or an acid solution with a concentration of 0.1 to 4 mol / L for 0.5 to 1.5 hours, wherein the acid solution is one of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.
[0028] Beneficial effects of the present invention:
[0029] (1) The present invention can effectively reduce the amount of washing solution through multi-stage countercurrent washing, and the washing solution sodium aluminate solution used can also be directly recycled to the alumina production process section.
[0030] (2) During the layered pretreatment, the washed lithium-rich adsorbent is treated with an oxidizing pretreatment solution. The oxidizing solution etches the lithium-rich adsorbent, and an adsorbent with a layered structure is obtained after solid-liquid separation. This layered structure allows the original lithium-rich adsorbent to have a larger specific surface area and active sites, making it easier to decompose lithium. At the same time, it can enhance the mechanical stability of the adsorbent and prevent the structural damage of the adsorbent during the decomposition process, thereby maintaining good decomposition properties; then, by mixing with an acidic solution, the carbonate and sulfide in the adsorbent are removed, making it easier to decompose lithium from the adsorbent; the decarbonized and desulfurized adsorbent is only heated once at 95 to 290°C for decomposition. After the hydrothermal transformation process, most of the lithium in the intercrystalline lattice can be precipitated as the structure changes, so that lithium can be efficiently decomposed, effectively reducing energy input.
[0031] (3) The present invention uses pre-stratification treatment and combines it with the desulfurization and decarbonization process to activate the adsorbent and improve the desorption efficiency. The process is simple and easy to control. The lithium-rich adsorbent in the alumina plant is pre-treated and activated, and on this basis, only one thermal desorption is used to obtain a higher desorption efficiency (>90%). Only one thermal desorption is used, the equipment investment is small, and energy consumption can be effectively reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.
[0033] Figure 1 This is a SEM electron microscope image of an adsorbent having a layered structure obtained after step S2 in Example 1;
[0034] Figure 2 The present invention is a process flow chart for analyzing lithium from lithium-rich adsorbent in an alumina plant. DETAILED DESCRIPTION
[0035] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0036] The lithium-rich adsorbents used in the present invention all come from alumina plants.
[0037] Example 1
[0038] S1. Washing of lithium-rich adsorbent:
[0039] The lithium-rich adsorbent is washed by a disc or crawler vacuum filter using deionized water in a continuous three-stage countercurrent washing manner, wherein the final washing liquid is a sodium aluminate solution with a mass fraction of 10%, to obtain the washed lithium-rich adsorbent and the final washing liquid.
[0040] S2, layered preprocessing:
[0041] At 20 °C, the washed lithium-rich adsorbent (Li 2 Al 0.1 (OH) 0.3 CO 3 , containing 0.1% sulfur) is immersed in a 10% by mass hydrogen peroxide solution for 5 hours, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with a hydrochloric acid solution to obtain an activated slurry, wherein the solid content of the activated slurry is 10%, and the pH value of the activated slurry is 3.56;
[0042] S3. Thermal analysis of activated slurry:
[0043] The activated slurry obtained in S2 is heated to 95° C. in a kettle hydrothermal reactor, kept at this temperature for 5 hours, and then cooled to 70° C., and the analyzed adsorbent and lithium-rich solution are obtained through solid-liquid separation;
[0044] S4, washing:
[0045] The analyzed adsorbent obtained in step S3 is first soaked in pure water for 1 hour, and then stirred and washed in a tank reactor to obtain an empty adsorbent and a washing solution. The washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0046] The lithium concentration in the lithium-rich solution obtained in this example is 2.1 g / L. After washing, an empty adsorbent is obtained, and the total lithium resolution is 95%. Figure 1 The electron microscopy image shows that the adsorbent obtained after pretreatment in step S2 has a layered structure.
[0047] Example 2
[0048] S1. Washing of lithium-rich adsorbent:
[0049] The lithium-rich adsorbent is washed with deionized water by a crawler vacuum filter in a continuous three-stage countercurrent washing manner, wherein the final washing liquid is a sodium aluminate solution with a mass fraction of 10%, thereby obtaining a washed lithium-rich adsorbent and a final washing liquid;
[0050] S2, layered preprocessing:
[0051] At 40 °C, the washed lithium-rich adsorbent (LiAl 2 / 3 (OH)CO 3, wherein the sulfide is contained in 2% by mass) is immersed in a sodium hypochlorite solution with a mass fraction of 10% for 0.2h, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with a nitric acid solution to obtain an activated slurry, wherein the solid content of the activated slurry is 50%, and the pH of the activated slurry is 2;
[0052] S3. Thermal analysis of activated slurry:
[0053] The activated slurry obtained in S2 is heated to 290° C. in a kettle hydrothermal reactor, kept at this temperature for 2 hours, and then cooled to 70° C., and the analyzed adsorbent and lithium-rich solution are obtained through solid-liquid separation;
[0054] S4, washing:
[0055] The analyzed adsorbent obtained in step S3 is first soaked in pure water for 1.5 hours, and then stirred and washed in a tank reactor to obtain an empty adsorbent and a washing solution. The washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0056] The lithium concentration in the lithium-rich analytical solution obtained in this example is 4.5 g / L. After washing, an empty adsorbent is obtained, and the total analytical rate of lithium is 98.2%.
[0057] Example 3
[0058] S1. Washing of lithium-rich adsorbent:
[0059] The lithium-rich adsorbent is washed by a crawler vacuum filter in a continuous five-stage countercurrent washing manner; deionized water is used to wash the lithium-rich adsorbent, and the final washing liquid is a sodium aluminate solution with a mass fraction of 18%, thereby obtaining the washed lithium-rich adsorbent and the final washing liquid;
[0060] S2, layered preprocessing:
[0061] At 50 °C, the washed lithium-rich adsorbent (Li 2 Al(OH) 3 CO 3 , containing 3% sulfur) is immersed in a nitric acid solution with a mass fraction of 8% for 1 hour, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with the nitric acid solution to obtain an activated slurry, wherein the solid content of the activated slurry is 40% and the pH of the activated slurry is 3.4;
[0062] S3. Thermal analysis of activated slurry:
[0063] The activated slurry obtained in S2 is heated to 240°C in a kettle hydrothermal reactor, kept at this temperature for 1 hour, and then cooled to 65°C, and the analyzed adsorbent and lithium-rich solution are obtained through solid-liquid separation;
[0064] S4, washing:
[0065] The analyzed adsorbent obtained in step S3 is first soaked in pure water for 1 hour, and then stirred and washed in a tank reactor to obtain an empty adsorbent and a washing solution. The washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0066] The lithium concentration in the lithium-rich analytical solution obtained in this example is 4.1 g / L. After washing, an empty adsorbent is obtained, and the total analytical rate of lithium is 97%.
[0067] Example 4
[0068] S1. Washing of lithium-rich adsorbent:
[0069] The lithium-rich adsorbent is washed by a crawler vacuum filter in a continuous four-stage countercurrent washing manner; deionized water is used to wash the lithium-rich adsorbent, and the final washing liquid is a sodium aluminate solution with a mass fraction of 12%, thereby obtaining the washed lithium-rich adsorbent and the final washing liquid;
[0070] S2, layered preprocessing:
[0071] At 70 °C, the washed lithium-rich adsorbent (Li 0.5 Al 2 (OH) 4.5 CO 3 , wherein the sulfide is 5% in weight) and immersed in a sodium hypochlorite solution with a mass fraction of 20% for 0.5 h, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with a sulfuric acid solution to obtain an activated slurry, wherein the solid content of the activated slurry is 6% and the pH of the activated slurry is 4.9;
[0072] S3. Thermal analysis of activated slurry:
[0073] The activated slurry obtained in S2 is heated to 280° C. in a kettle hydrothermal reactor, kept at this temperature for 1 hour, and then cooled to 60° C., and the analyzed adsorbent and lithium-rich solution are obtained through solid-liquid separation;
[0074] S4, washing:
[0075] The analyzed adsorbent obtained in step S3 is first soaked in 0.1 mol / L nitric acid for 0.8 h, and then washed by a crawler vacuum filter to obtain an empty adsorbent and a washing solution. The washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0076] The lithium concentration in the lithium-rich analytical solution obtained in this example is 1.9 g / L. After washing, an empty adsorbent is obtained, and the total analytical rate of lithium is 92%.
[0077] Example 5
[0078] S1. Washing of lithium-rich adsorbent:
[0079] The lithium-rich adsorbent is washed by a crawler vacuum filter in a continuous three-stage countercurrent washing manner; deionized water is used to wash the lithium-rich adsorbent, and the final washing liquid is a sodium aluminate solution with a mass fraction of 20%, thereby obtaining a washed lithium-rich adsorbent;
[0080] S2, layered preprocessing:
[0081] At 80 °C, the washed lithium-rich adsorbent (Li 0.6 Al(OH) 1.6 CO 3 , wherein the sulfide is contained in 3% by mass) and immersed in a 5% by mass hydrogen peroxide solution for 1 hour, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with an acetic acid solution to obtain an activated slurry, wherein the solid content of the activated slurry is 15%, and the pH of the activated slurry is 3.9;
[0082] S3. Thermal analysis of activated slurry:
[0083] The activated slurry obtained in S2 is heated to 220° C. in a kettle hydrothermal reactor, kept at this temperature for 1 hour, and then cooled to 50° C., and the analyzed adsorbent and lithium-rich solution are obtained through solid-liquid separation;
[0084] S4, washing:
[0085] The analyzed adsorbent obtained in step S3 is first soaked in a 2 mol / L sulfuric acid solution for 0.5 h, and then washed by a crawler vacuum filter to obtain an empty adsorbent and a washing solution. The washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0086] The lithium concentration in the lithium-rich analytical solution obtained in this example is 2.2 g / L. After washing, an empty adsorbent is obtained, and the total analytical rate of lithium is 92%.
[0087] Example 6
[0088] S1. Washing of lithium-rich adsorbent:
[0089] The lithium-rich adsorbent is washed by a crawler vacuum filter in a continuous three-stage countercurrent washing manner; deionized water is used to wash the lithium-rich adsorbent, and the final washing liquid is a sodium aluminate solution with a mass fraction of 5%, thereby obtaining the washed lithium-rich adsorbent and the final washing liquid;
[0090] S2, layered preprocessing:
[0091] At 60 °C, the washed lithium-rich adsorbent (Li 2 Al(OH)3 CO 3 , wherein the sulfide is contained in 3% by mass) is immersed in a nitric acid solution with a mass fraction of 20% for 0.5h, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with a hydrochloric acid solution to obtain an activated slurry, wherein the solid content of the activated slurry is 30%, and the pH of the activated slurry is 2.9;
[0092] S3. Thermal analysis of activated slurry:
[0093] The activated slurry obtained in S2 is heated to 200° C. in a kettle hydrothermal reactor, kept at this temperature for 1.5 h, and then cooled to 50° C., and the analyzed adsorbent and lithium-rich solution are obtained through solid-liquid separation;
[0094] S4, washing:
[0095] The analyzed adsorbent obtained in step S3 is first soaked in an acetic acid solution with a concentration of 4 mol / L for 1 hour, and then washed with a crawler vacuum filter to obtain an empty adsorbent and a washing solution. The washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
[0096] The lithium concentration in the lithium-rich analytical solution obtained in this example is 2.0 g / L. After washing, an empty adsorbent is obtained, and the total analytical rate of lithium is 92%.
[0097] Comparative Example 1
[0098] The difference between Comparative Example 1 and Example 1 is that the step S2 is not performed in Comparative Example 1, and the other operations are the same.
[0099] The lithium concentration in the lithium-rich analytical solution obtained in this comparative example was 0.5 g / L. After washing, an empty adsorbent was obtained, and the total analytical rate of lithium was 80%.
[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for analyzing lithium from a lithium-rich adsorbent in an alumina plant, characterized in that: The process includes: S1. Washing of lithium-rich adsorbent: The lithium-rich adsorbent is washed with deionized water by a disc or crawler vacuum filter in a continuous multi-stage countercurrent washing manner, and the washing liquid of the previous stage washes the adsorbent of the next stage to obtain the washed lithium-rich adsorbent and the final washing liquid; S2, layered preprocessing: At 20 to 80° C., the washed lithium-rich adsorbent is immersed in a pretreatment solution for 0.2 to 5 hours, and then an adsorbent with a layered structure is obtained by solid-liquid separation, and the adsorbent with a layered structure is mixed with an acidic solution to obtain an activated slurry, wherein the solid content of the activated slurry is 6 to 50%; S3. Thermal analysis of activated slurry: The activated slurry obtained in S2 is heated to 95-290° C., kept at this temperature for 1-5 hours, and then cooled to 50-70° C. to obtain an analyzed adsorbent and a lithium-rich solution through solid-liquid separation; S4, washing: The analyzed adsorbent obtained in step S3 is subjected to multi-stage washing to obtain an empty adsorbent and a washing solution, and the washing solution and the lithium-rich solution obtained in step S3 are mixed to obtain a lithium-rich analyzed solution.
2. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S1, the lithium-rich adsorbent is a lithium-aluminum composite adsorbent, and its composition is (Li x Al y (OH) z CO3), wherein x=0.5-2, y=0.1-2, z=0.3-4.5, and contains 0.1-5% sulfur or sulfide.
3. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S1, the number of stages of the continuous multi-stage countercurrent washing is 3 to 5.
4. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S1, the final washing liquid is a sodium aluminate solution with a mass fraction of 5 to 20%.
5. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S2, the pretreatment liquid is an oxidizing solution with a mass fraction of 5-20%, which is one or more of hydrogen peroxide, sodium hypochlorite and nitric acid.
6. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S2, the acidic solution is one or more of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.
7. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S2, the pH value of the activated slurry is 1.4-4.
9.
8. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S3, the equipment used for heating is a kettle hydrothermal reactor or a pipeline hydrothermal reactor.
9. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S4, the multi-stage washing method is to use a tank reactor stirring washing or a vacuum crawler elution washing.
10. The method for decomposing lithium from lithium-rich adsorbent in an alumina plant according to claim 1, characterized in that: In step S4, before the multi-stage washing, the product is first soaked in pure water or an acid solution with a concentration of 0.1 to 4 mol / L for 0.5 to 1.5 hours, wherein the acid solution is one of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.
